Siti Jenar: Perebutan Hegemoni Agama dan Kekuasaan di Jawa. (Siti Jenar:The seizing of religion and power hegemony in Java) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Siti Jenar that discloses a story of Syekh Siti Jenar confronting with Wali Sanga is a myth in Javanese realm. The myth that has been known widely by people â because it had been filmed before â involved Ki Ageng Pengging and Kanjeng Sultan Bintara in Demak. The binary opposition between the two groups is stated by Mu lkan as a fighting over religion and politic hegeÂ¬mony. To reveal the various binary opposition and to interpret them, it is used a structural analisys strategy similar to Levi-Strauss', as what AhimsaÂ¬Putra developed. The strategy could reveal a human mind structure dan innate of Javanese people to face conflicts, as keeping a harmony and equalÂ¬izing by raising a mediator figure (Mas Karebet), a son of Ki Ageng Pengging and also a son in law of Kanjeng Sultan Bintara. The raising of the figure was also a signal of Islam victory in Java spread by Syekh Siti Jenar.